2012
DOI: 10.1016/j.ophtha.2012.01.050
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Cataract and Cataract Extraction to Age-related Macular Degeneration: The Beaver Dam Eye Study

Abstract: Objective To examine the associations of cataract and cataract surgery with early and late age-related macular degeneration (AMD) over a 20-year interval. Design Longitudinal population-based study of age-related eye diseases. Participants: Beaver Dam Eye Study participants. Methods All persons 43-84 years of age were recruited in 1987-1988. Participants were followed up at five year intervals after the baseline examination in 1988-1990. Examinations consisted of ocular examination with lens and fundus pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 27 publications
2
51
0
1
Order By: Relevance
“…22 Furthermore, Klein et al observed a clear association between cataract surgery and late AMD independently of other risk factors, including a highrisk genetic status. 41 They emphasize the importance of considering these findings when counseling patients on a cataract surgery. Their data is in line with a recent meta-analysis that considers previous cataract surgery as a consistent risk factor for AMD.…”
Section: Hormone Therapy and Menopause In Amdmentioning
confidence: 99%
“…22 Furthermore, Klein et al observed a clear association between cataract surgery and late AMD independently of other risk factors, including a highrisk genetic status. 41 They emphasize the importance of considering these findings when counseling patients on a cataract surgery. Their data is in line with a recent meta-analysis that considers previous cataract surgery as a consistent risk factor for AMD.…”
Section: Hormone Therapy and Menopause In Amdmentioning
confidence: 99%
“…The authors have continued to update their findings at five-year intervals and these statistical findings are detailed in Table 1. 8,32 In the Australian Blue Mountains Eye Study of 2454 participants, although initial cross-sectional analysis indicated no association between cataract and AMD, 33 the investigators noted a three-fold increase at 10 years of developing late AMD in those with a history of previous cataract surgery (Odds ratio (OR) 3.3 [95% confidence interval (CI) 1.1-9.9]). 7 In particular, this effect was most pronounced for nAMD ( …”
Section: Evidence Suggesting An Association Between Cataract Surgery mentioning
confidence: 99%
“…[1][2][3][4] Meanwhile, cataract progression is the most widespread cause of blindness worldwide, affecting nearly 20 million people. 1,2,[5][6][7][8][9][10][11][12][13][14] Cataract surgery remains the only treatment available to definitively remove lens opacification once visual decline has occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests increases in both the incidence and progression rate of diabetic retinopathy at 1 year after phacoemulsification cataract surgery, and findings are inconsistent from large studies about the association between cataract surgery and long-term risk for the development of either early or late AMD. [16][17][18] It is clearer that the risk of post-surgical cystoid macular edema is increased in patients with a history of retinal vein occlusion or epiretinal membrane. 19 Given the totality of the available evidence and our own experience, we are very conservative in the presence of retinal findings and maintain a low threshold for referral to a retinal specialist for further evaluation, including a dilated fundus exam and OCT, and potential treatment (see Figures 3 and 4).…”
mentioning
confidence: 99%